Adsorptive Performance of Gelatin-Hematite Composite Synthesized from Iron Lathe Waste Using Guava Leaf Extract for Pb(II) Removal from Aqueous Solutions - Khoiroh, Lilik Miftahul; Barroroh, Himmatul; Taufik, Moh; Royyanuddin, Moh; Al Akbar, Ramadhana Fatahillah; Amaliyah, Nada Rifqi; Yulianti, Eny (al Kimiya: Jurnal Ilmu Kimia dan Terapan, 2025)
Hematite was successfully synthesized from iron lathe waste using guava leaf extract as a reducing agent. To enhance adsorption capacity, hematite was composited with gelatin, a polymer containing amide and carboxylate functional groups. The hematite-gelatin composite was employed as an adsorbent for Pb solutions. This study investigated the material's structure and the adsorbent's performance, including the composite's optimum dosage and contact time. Characterization techniques included XRD, FTIR, SEM-EDX, and AAS analyses. XRD analysis revealed that the hematite-gelatin composite exhibited a high degree of crystallinity. FTIR analysis of the guava leaf extract spectrum identified phenolic vibrational absorption with strong intensity at 3447 cm-1 (O-H stretching) and a weak C-H vibrational bond at 2928 cm-1. An ester group (C=O) at 1726 cm-1 indicated the presence of tannin compounds. For the hematite-gelatin composite, a C-O absorption band was observed at 1075 cm-1, along with Fe-O absorption bands at 430 and 519 cm-1. The SEM results show that the gelatin-hematite composite has a hollow and layered surface. The EDX analysis results show that the material contains C, N, O, Pb, and Fe, which indicates that gelatin has interacted with Pb when it becomes a composite and has absorbed Pb at a level of 1.4% after adsorption. Performance evaluation of the hematite-gelatin composite demonstrated high adsorption efficiency for Pb solutions. The adsorbent exhibited a high adsorption capacity of 800 mg/g with an optimal adsorbent dosage of 15 ppm and an optimal contact time of 70 minutes. The adsorption kinetics of the hematite-gelatin composite followed a pseudo-first-order adsorption model.